2008
DOI: 10.1016/j.cellsig.2007.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Role of chimaerins, a group of Rac-specific GTPase activating proteins, in T-cell receptor signaling

Abstract: Chimaerins are GTPase-activating proteins that inactivate the GTP-hydrolase Rac1 in a diacylglycerol-dependent manner. To date, the study of chimaerins has been done mostly in neuronal cells. Here, we show that α2-and β2-chimaerin are expressed at different levels in T-cells and that they participate in T-cell receptor signaling. In agreement with this, we have observed that α2-and β2-chimaerins translocate to the T-cell/B-cell immune synapse and, using both gain-and loss-offunction approaches, demonstrated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 57 publications
2
21
0
2
Order By: Relevance
“…Using luciferase reporter assays, we first examined the effect of WT ␤2-chimaerin and the Y153F mutant on NF-AT activity. As reported previously (25), ␤2-chimaerin overexpression clearly reduced NF-AT activity after stimulation of Jurkat T cells with anti-CD3 or -CD3/CD28 Ab (Fig. 3B).…”
Section: Tcr Triggering Induces Tyr Phosphorylation Of ␤2-chimaerin-␤supporting
confidence: 64%
See 2 more Smart Citations
“…Using luciferase reporter assays, we first examined the effect of WT ␤2-chimaerin and the Y153F mutant on NF-AT activity. As reported previously (25), ␤2-chimaerin overexpression clearly reduced NF-AT activity after stimulation of Jurkat T cells with anti-CD3 or -CD3/CD28 Ab (Fig. 3B).…”
Section: Tcr Triggering Induces Tyr Phosphorylation Of ␤2-chimaerin-␤supporting
confidence: 64%
“…, where it is proposed to regulate Rac activation during T cell synapse formation (25). Moreover, a recent study using COS-1 cells showed that Src-dependent tyrosine phosphorylation negatively regulates ␤2-chimaerin Rac-GAP functions (31).…”
Section: Tcr Triggering Induces Tyr Phosphorylation Of ␤2-chimaerin-␤mentioning
confidence: 99%
See 1 more Smart Citation
“…9). Likewise, chimaerins, a group of DAGdependent Rac1 GTPase-activating proteins, have been shown to inhibit Vav-mediated responses in T-lymphocytes (54).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that T cell receptor engagement by antigen promotes the rapid activation of these GTPases together with an array of other signaling molecules (12,13). Subsequently, Rac proteins transduce signals through intermediate signaling molecules, most notably PKC (14), phosphatidylinositol 3-kinase (PI3K) (5), calcium (15), and PLC␥1 (13). Importantly, Rac1 controls the translocation of RasGRP1 (a guanine nucleotide exchange factor for Ras) to the actin juxtamembrane structures to facilitate Ras/ERK pathway activation (12).…”
mentioning
confidence: 99%